Performance of Tourism Competitiveness in National Park Area of Indonesia - EDDYONO, Fauziah; DARUSMAN, Dudung; SUMARWAN, Ujang; SUNARMINTO, Tutut (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).22, 2021)
Essentially tourism Indonesia has certain excellence natural attraction wealth, one of them is the largest tropical forest products after Brazil and having 54 national parks. This country also has a nature property and the diversity of culture, typical living culture and a bonus of demographic to participate in tourism. Nowadays, Indonesian government is setting a tourism sector as one of a priority program. Measuring the performance of the tourism sector is not only measured by the number of tourists visit but the impact of the tourism sector is also to be able to become income sources and income in the region. Therefore, we present an assessment regarding to a potential correlation and characteristics of the tourism competitiveness through a non-tax income receipts on the site of a national park, and local government revenue, and tourist arrival at districts with its national park in Indonesia. We employ method of clusters and canonical correlation analysis. As results, we formed 3 (three) clusters of areas that have a national park based on the characteristics of potential tourism competitiveness. From these clusters, the tourism competitiveness, the most superior factor is security purchasing power parity, price competitiveness, tourist service infrastructure, openness indicator, environment indicator, and social development indicator. We conclude finally that none of the competitiveness of tourism in the region has a strong correlation in the non-tax income on the site of a national park, and local government revenue, and tourist’s arrival in districts with its a national park in Indonesia.